Exploring genome-wide – dietary heme iron intake interactions and the risk of type 2 diabetes - Pasquale, Louis R.; Loomis, Stephanie; Aschard, Hugues; Kang, Jae Hee; Cornelis, Marilyn C.; Qi, Lu; Kraft, Peter; Hu, Frank (Frontiers in Genetics, 2013)
Aims/hypothesis: Genome-wide association studies have identified over 50 new genetic loci for type 2 diabetes (T2D). Several studies conclude that higher dietary heme iron intake increases the risk of T2D. Therefore we assessed whether the relation between genetic loci and type 2 diabetes is modified by dietary heme iron intake. Methods: We used Affymetrix Genome-Wide Human 6.0 array data (681,770 single nucleotide polymorphisms (SNPs)) and dietary information collected in the Health Professionals Follow-up Study (n=725 cases; n=1,273 controls) and the Nurses’ Health Study (n=1,081 cases; n=1,692 controls). We assessed whether genome-wide SNPs or iron metabolism SNPs interacted with dietary heme iron intake in relation to T2D, testing for associations in each cohort separately and then meta-analyzing to pool the results. Finally, we created 1,000 synthetic pathways matched to an iron metabolism pathway on number of genes, and number of SNPs in each gene. We compared the iron metabolic pathway SNPs with these synthetic SNP assemblies in their relation to T2D to assess if the pathway as a whole interacts with dietary heme iron intake. Results: Using a genomic approach, we found no significant gene-environment interactions with dietary heme iron intake in relation to T2D (top SNP in pooled analysis: intergenic rs10980508; p=1.03E-06 > Bonferroni corrected p=7.33E-08). Furthermore, no SNP in the iron metabolic pathway significantly interacted with dietary heme iron intake (top SNP in pooled analysis: rs1805313; p=1.14E-03 > Bonferroni corrected p=2.10E-04). Finally, neither the main genetic effects (pooled empirical p by SNP=0.41), nor gene – dietary heme-iron interactions (pooled empirical p value for the interactions=0.72) were significant for the iron metabolic pathway as a whole. Conclusions: We found no significant interactions between dietary heme iron intake and common SNPs in relation to T2D.